2012
DOI: 10.1371/journal.pone.0042768
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation into the Impact of a Pesticide Combination on Human Neuronal and Glial Cell Lines In Vitro

Abstract: Many pesticides are used increasingly in combinations during crop protection and their stability ensures the presence of such combinations in foodstuffs. The effects of three fungicides, pyrimethanil, cyprodinil and fludioxonil, were investigated together and separately on U251 and SH-SY5Y cells, which can be representative of human CNS glial and neuronal cells respectively. Over 48h, all three agents showed significant reductions in cellular ATP, at concentrations that were more than tenfold lower than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 57 publications
4
37
0
1
Order By: Relevance
“…Results from these viability experiments showed that neurons are more sensitive to cytotoxic effects of agents tested in all cases excepting for GF, which induces similar cytotoxicity in both cell types. This agrees with previous studies generally showing more sensitivity of neuronal cells to cytotoxicity induction as compared to glial cells (Coccini et al, 2015;Coleman et al, 2002;Rovetta et al, 2007). The relatively higher resistance of A172 cells to toxicity compared with the SH-SY5Y cells reflects to some extent the role of astrocytes in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results from these viability experiments showed that neurons are more sensitive to cytotoxic effects of agents tested in all cases excepting for GF, which induces similar cytotoxicity in both cell types. This agrees with previous studies generally showing more sensitivity of neuronal cells to cytotoxicity induction as compared to glial cells (Coccini et al, 2015;Coleman et al, 2002;Rovetta et al, 2007). The relatively higher resistance of A172 cells to toxicity compared with the SH-SY5Y cells reflects to some extent the role of astrocytes in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…However, since they have different purpose in the organism, they are expected to respond to neurotoxic insults in a disparate way, making it difficult to establish the neurotoxic risk of one specific agent. Indeed, the diverse response of these cells against the same external insult (Coccini et al, 2015;Coleman et al, 2002), and also the different effects manifested regarding cells from other origins (e.g., hepatocytes, kidney cells, lymphocytes, skeletal muscle cells, etc.) (Rovetta et al, 2007;Valdiglesias et al, 2010) have been previously documented, supporting the relevance of employing particularly nervous system cell types for testing the toxicity of chemicals suspicious of being able to cross the bloodbrain barrier (e.g., nanomaterials).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were then stimulated by experimental treatment medium for 48 h. The cells were washed twice with serumfree medium and incubated with a final concentration of 1 µM JC-1 (5,5',6,6'-tetrachloro-1,1',3,3'-tetraethylbenzimidazolylcarbocyanine iodide) in DMEM medium for 30 min at 37˚C and 5% CO 2 (17,18). After the medium was removed, each treatment group of cells was washed with PBS 3 times, and 100 µl of PBS was added to each well.…”
Section: Mitochondrial Membrane Potential Detection By Jc-1 Stainingmentioning
confidence: 99%
“…To follow the effect of pesticide poisioning in human body can cause a decrease of cholinesterase levels in the blood. [25], [26].…”
mentioning
confidence: 99%